Biodiesel Production by Transesterification of Waste Cooking Oil Using Modified Attapulgite. - Mabungela, Ntandokazi (Vaal University of Technology, 2019)
Biodiesel has an ability to solve the problem associated with the use of fossil fuels as a source of energy. The aim of this study was to produce biodiesel from waste cooking oil (WCO) by transesterification, catalysed with potassium hydroxide (KOH) supported on attapulgite (ATP) clay as the heterogeneous catalyst. WCO was used on the basis that it is one of the cheapest feedstocks for biodiesel production, is readily available and can minimise environmental impact. ATP clay was first crushed and sieved to particle sizes of ≤ 90 μm and subsequently treated with hydrochloric acid (HCl) to remove impurities. The KOH supported ATP catalyst was prepared through ion exchange method by soaking ATP into KOH solution, dried in an oven and later calcined at 400 ℃ in a furnace. The prepared catalyst and ATP clay were characterised using Hammett indicator to determine the basic strength of the catalyst. XRF and EDX were used to determine the elemental composition of the catalyst whilst XRD was used to determine the crystallinity of the ATP after modification. The functional groups of ATP were determined by FTIR. BET was utilised to determine the changes on the surface area, pore volume and pore diameter of ATP and on the other hand, SEM was used to determine the morphological changes on the surface of ATP. The XRD, FTIR, BET AND SEM-EDX showed that addition of potassium caused changes on the surface of the ATP. The optimal conditions for the transesterification reaction of waste cooking oil with methanol were found to be oil-to-methanol molar ratio of 1:15, 3wt% catalyst amount, 65 ℃, 3 h of a reaction time, at 200 rpm stirring rate and 94 % biodiesel yield was obtained. After the catalyst was reuse three consecutive times, the decrease in biodiesel yield was observed (Figure 17) after each cycle. However, the 5MKOH/ATP catalyst is heterogeneous and can be used to transesterify WCO with good yield.
M. Tech. (Department of Chemistry, Faculty of Applied And Computer Sciences), Vaal University of Technology.
Keywords: Biodiesel; Transesterification of waste cooking oil; Attapulgite; Dissertations, Academic -- South Africa; Biodiesel fuels; Transesterification; Vegetable oils